Investigación histórica de las campañas de prospección geoquímica en el Ecuador - Andrade Mantilla, Fernanda Dayana (2024)
This research collects bibliographic information from Geochemical Prospecting campaigns carried out in Ecuador from 1970 to the present. Through this work, historical research is summarizes, compiling information from several projects carried out with different technical cooperation, however, the British Geological Survey (1998-2000) stands out among the main ones, since through the PRODEMINCA project it covered the entire Western Cordillera and collected 15 175 samples of stream sediments, marking a precedent in the historical trajectory in the search for mineral occurrences. Currently, the project “Geological investigation and availability of mineral resource occurrences in Ecuadorian territory” is updating the geochemical information of the territory, specifically within the reference area that covers the Cordillera Real and the Subandean Zone, which includes an area of 140 932,69 km2, for which it has taken existing information as a basis, it currently has a total of 15 178 samples of stream sediments, collected with internationally standardized practices and applied by the PRODEMINCA Project, it is important to highlight that upon completion of its execution, will provide a database that will serve as a guide to explore potential new mineral deposits through mining exploration activities on a regional scale.